Mechanism of anti-remodelling action of treprostinil in human pulmonary arterial smooth muscle cells. - Christopher Lambers; Christoph Kornauth; Felicitas Oberndorfer; Panja M Boehm; Michael Tamm; Walter Klepetko; Michael Roth (PLoS ONE, 2018)
Treprostinil is applied for pulmonary arterial hypertension (PAH) therapy. However, the mechanism by which the drug achieves its beneficial effects in PAH vessels is not fully understood. This study investigated the effects of treprostinil on PDGF-BB induced remodelling parameters in isolated human pulmonary arterial smooth muscle cells (PASMC) of four PAH patients. The production of TGF-β1, CTGF, collagen type-I and -IV, and of fibronectin were determined by ELISA and PCR. The role of cAMP was determined by ELISA and di-deoxyadenosine treatment. Proliferation was determined by direct cell count. Treprostinil increased cAMP levels dose and time dependently, which was not affected by PDGF-BB. Treprostinil significantly reduced PDGF-BB induced secretion of TGF-β1 and CTGF, both was counteracted when cAMP generation was blocked. Similarly, the PDGF-BB induced proliferation of PASMC was dose dependently reduced by treprostinil through signalling via cAMP-C/EBP-α p42 -p21(WAf1/Cip1). In regards to extracellular matrix remodelling, treprostinil significantly reduced PDGF-BB-TGF-β1-CTGF induced synthesis and deposition of collagen type I and fibronectin, in a cAMP sensitive manner. In contrast, the deposition of collagen IV was not affected. The data suggest that this action of treprostinil in vessel wall remodelling may benefit patients with PAH and may reduce arterial wall remodelling.